Behavioural economics and finance - Baddeley, Michelle (London, 2013)
Standard models in economics and finance usually assume that people are rational, self-interested maximisers, effectively co-ordinated via the invisible hand of the price mechanism. Whilst these approaches produce tractable, simple models, they cannot fully capture the uncertainties and instabilities that affect everyday choices in today$1 (Bs complex world. Insights from the other social and behavioural sciences can help to fill the gap and behavioural economics is the subject which brings economics and finance together with psychology, neuroscience and sociology. Behavioural Economics and Finance introduces the reader to some of the key concepts and insights from this rich, inter-disciplinary approach to real-world decision-making.s
Keywords: Economics-Psychological aspects